The investigations on experimııntal colibasillosis and its treatment with milk replacer samples in calves - Yeysi ASLAN; Yavuz SEZEN; Osman ERGANİŞ; Ali Muhtar TİFTİK; Osman KAYA (Eurasian Journal of Veterinary Sciences)
Twelve calves about one week old, were usercl in this study. Milk replacer was given with special bucket. Before inoculating E. coli strains, the calves were examined clinically and pocket cell volume (PCV), total leucocyt number, serum urea, Na, K, inorganic P and total protein were determined in blood samples. All of these blood parameters were found in normal values. Each calves was given orally 40 ml. enterötoxigenic (108- bacterins/ ml.) and 2 ml. invasion (l012bacterins/ml.) E. coli strain for occuring experimental colibasillosis. All calves were examined clinically and their blood samples were taken for determining blood parameters at 1st, 12th, 36th hour of infection. At 12th hour of infection elinical signs were observed. They were fever, lock of appetite, mild diarrhoea and increased pulse and respiratory rate. At 36th hour these elinical findings were became severe. At the same time PCV, total leucocyt, serum urea levels were increased and Na level was decreased significantly. However, the total protein, K and P values were not affected. After the observation of these sing the calves were divided into three groups: The control, Esha Calvasid Superasid and Cholostral Suplement groups. The calves in control group were given 150g/l water Esha calvasid 60, the calves in other treatment group were given 125g/l water Esha calvasid superasid and the•third group w as fed 50 ml. cholostral suplement/1 milk. Only one calf in control•group died and other calves in control group were heated with cholostral suplement. The calves in both tteatment group were returned to their normal health.